Yersinia pseudotuberculosis infection in four free-ranging odontocetes - Nicholas J. Davison; Stephen A. Raverty; Els M. Broens; Andrew C. Brownlow; Mark P. Dagleish; Andrea Gröne; Marja J.L. Kik; Linde van Schalkwijk; Lonneke L. IJsseldijk (Journal of Comparative Pathology, 2026)

Insights into anthropogenic threats and early mortality in the Guadalupe fur seal from a plausible mixed colony on the San Benito Archipelago, Mexico - Casandra Gálvez; Fernando R. Elorriaga-Verplancken; Claudia J. Hernández-Camacho; Arturo B. Enríquez-García; Stephen Raverty; Germán Ponce-Díaz; Ernesto I. Popoca-Arellano (Frontiers in Marine Science, 2026)
In Mexico, the Guadalupe fur seal ( Arctocephalus townsendi , GFS) is listed as Risk of Extinction, with one breeding site on Guadalupe Island, and another potential colony proposed in the late 1990s on the San Benito Archipelago (SBA). Although there are some health and mortality studies regarding GFS on Guadalupe Island, the SBA colony remains understudied. This study aimed to characterize the causes of neonatal GFS morbidity and mortality, and to assess potential threats to species conservation associated with entanglement, alopecia syndrome, and marine pollution on the West Island of the SBA during the 2024 breeding season. Field data on total births and neonate mortalities were collected during the first 30 days of life. Entanglement and alopecia syndrome incidents were recorded and analyzed to determine age class and sex predilection using Bayesian analyses. Also, marine pollution was classified and quantified by environmental debris type. The neonatal mortality rate in GFS was 29.52%. Perinate deaths were considered natural and attributed to trauma (50%) and emaciation/infectious disease (50%). The prevalence of the alopecia syndrome in non-pup GFSs was high (21% to 26%) during the 2024 breeding season. Clinically, there were bilateral and asymmetrical presentations, with a higher probability of detection of this syndrome in yearlings and juveniles, particularly in males. Entanglements were related to marine debris (100%), affecting juvenile individuals (80%) and adults (20%). A field survey of the composition of marine debris along the SBA beaches revealed that 92% was plastic, predominantly bottles (65%) and fishing gear (16%). Local or regional sources appear to contribute to pollution in the SBA based on the composition of the debris and its proximity to human habitation. Mortality and alopecia rates in immature GFSs were much higher compared to Guadalupe Island, identifying potential challenges in health and survival during early development stages in the SBA. The establishment of the GFS population in the SBA spans almost three decades; however, key demographic factors remain undetermined. Continued efforts to characterize the factors limiting the transition of the SBA from a plausible mixed to a breeding colony are warranted.

3D reconstructions of stranded marine mammals via easily accessible remote sensing tools for use in morphometrics and visualizations - Brendan Cottrell; Margaret Kalacska; J. Pablo Arroyo-Mora; Oliver Lucanus; Paul Cottrell; Taylor Lehnhart; Stephen Raverty (Frontiers in Marine Science, 2025)
This study investigates the practicality and potential impact of three-dimensional (3D) scanning technology to assess marine mammal strandings. Mobile phones were used to evaluate the technology and its capability to accurately reconstruct topographic features of 11 distinct marine mammal species, across diverse environmental conditions. This process was validated by initially measuring an inflatable whale to an accuracy of greater than 99%, with most morphometrics collected being within 3% of conventional tape rule measurements. Our findings demonstrate the adaptability of the technology in remote environments, particularly for large whale strandings, while showcasing its utility to record morphometrics and enhance necropsy documentation. The study underscores the transformative role of 3D scanning in marine mammal postmortem examinations and conservation efforts, offering avenues for improved research, education, and management practices. It emphasizes the importance of accessible technology in engaging communities and advancing wildlife conservation efforts globally.

Harassment and killing of porpoises (“phocoenacide”) by fish‐eating Southern Resident killer whales ( Orcinus orca ) - Deborah A. Giles; Sarah J. Teman; Samuel Ellis; John K. B. Ford; Monika W. Shields; M. Bradley Hanson; Candice K. Emmons; Paul E. Cottrell; Robin W. Baird; Richard W. Osborne; Michael Weiss; David K. Ellifrit; et al. (Marine Mammal Science, 2024)
Endangered Southern Resident killer whales ( Orcinus orca ) are fish‐eaters that preferentially prey on adult Chinook salmon ( Oncorhynchus tshawytscha ). Despite being salmon specialists, individuals from all three killer whale pods (J, K, L) have been observed harassing and killing porpoises (family Phocoenidae) without consuming them. Retrospectively, we identified and analyzed 78 episodes of Southern Resident killer whales harassing porpoises between 1962 and 2020, of which 28 resulted in the porpoise's death (“phocoenacide”). Fifty‐six episodes involved harbor porpoise ( Phocoena phocoena ), 13 involved Dall's porpoise ( Phocoenoides dalli ), and the porpoise species was unreported for nine episodes. Southern Resident killer whales often targeted young porpoises that were similar in size to adult Chinook salmon. Both sexes participated in porpoise harassment. Juveniles engaged in the behavior the most; however, their rates of engagement were not found to differ significantly from most other age classes. The behavior was passed through generations and social groupings, as it was first observed in L pod and spread to the other two pods. Killer whales are highly complex animals known to exhibit social learning and cultural transmission of learned behaviors, but the reason(s) for this behavior is unknown. Hypotheses include the social and developmental benefits of play, hunting practice, or displaced epimeletic behavior.

Mortality in an off-shore predator critical habitat during the Northeast Pacific marine heatwave - Casandra Gálvez; Stephen Raverty; Felipe Galván-Magaña; Cara L. Field; Fernando R. Elorriaga-Verplancken (Frontiers in Marine Science, 2023)
Defining baseline mortality and trends in wildlife populations is imperative to understand natural and anthropogenic threats to overall population health and improve conservation measures for species, particularly in geographically confined habitats. The Guadalupe fur seal Arctocephalus townsendi (GFS) is a threatened pinniped that ranges throughout the west coast of Mexico with sporadic dispersion to higher latitudes. Their breeding habitat is restricted to Guadalupe Island, Mexico, which is vulnerable to periodic and cyclic warming of the Northeast Pacific Ocean. The impacts of environmental change on GFS health and reproductive success at Guadalupe Island are poorly defined and the aim of this study was to establish baseline pup (GFS n ) mortality rates and primary causes of death during the 2013-2016 breeding seasons at Guadalupe Island. Interannual mortality rates and causes of death were compared by year, breeding seasons and by geographic location. The highest mortality rate in GFS n was in 2015 (14.7%), followed by 2014 (8.2%), 2016 (6.7%) and 2013 (5.6%). The presumptive causes of mortality of GFS n were consistent with other published long term otariids health surveys and included: emaciation (49%), trauma (24%), infectious disease (8%), drowning (4%) stillbirth/perinatal mortality (4%) and undetermined (11%). However, in 2015 and coinciding with northeast Pacific marine heatwave in 2014-2016, emaciation accounted for 54% of GFS n mortality in contrast to 9% in 2013. For GFS n , terrestrial habitat may influence mortality rates and causes of mortality but like other marine predators, marine habitat features, such as an increase in sea surface temperature are associated with changes in maternal care, nutritional status and pups survival. Monitoring mortality rate and causes in GFS n at Guadalupe Island is crucial to establish baseline health trends, document potential impacts on species demographics and recruitment during marine heatwaves and potential consequences in population recovery.

Risk factor determination and qualitative risk assessment of Mucormycosis in Harbor Porpoise, an emergent fungal disease in Salish Sea marine mammals - Stephanie A. Norman; Jessica L. Huggins; Dyanna M. Lambourn; Linda D. Rhodes; Michael M. Garner; Jennie L. Bolton; Joseph K. Gaydos; Alyssa Scott; Stephen Raverty; John Calambokidis (Frontiers in Marine Science, 2022)
Mucorales infections are increasing in frequency and are a One Health pathogen of concern. In humans and domestic animals, risk factors include being immunocompromised, elevated circulating serum iron, contaminated open wounds, or metabolic diseases such as ketoacidosis or uncontrolled diabetes. Mucormycosis was first identified in 2012 in Pacific Northwest marine mammals, predominantly in harbor porpoises. We performed an assessment to determine the overall qualitative risk, or risk score, of mucormycosis in harbor porpoises. Risk factors for this disease are unknown in aquatic mammals. In a separate risk factor analysis, potential risk factors such as pollutants, trace metals (e.g., iron), and co-infection with other pathogens (e.g., viruses and Brucella spp.) were examined in mucormycosis cases and noncases using a matched case-control study design, to determine the presence and strength of association of these factors with mucormycosis. Disease severity (gross and histopathology) and exposure scores were multiplied together to obtain the overall risk scores of 9 -16 which corresponded to moderate and severe, respectively. In the risk factor analysis, the factors most strongly associated with a mucormycosis case, relative to a control, were elevated liver iron, decreased blubber thickness, and the decreased ratio of the sum of PCB congeners/sum of PBDE congeners. The results of this study suggest that mucormycosis may pose an inordinately high risk to harbor porpoises (and potentially sympatric species in the Salish Sea such as southern resident killer whales) based on the detected prevalence and the severity of lesions observed at necropsy. However, the risk may be greater on an individual basis compared to the overall population, and is likely related to other factors such as increased POP and heavy metal burdens.

Editorial: Pathologic Findings in Stranded Marine Mammals: A Global Perspective - Debra L. Miller; Alvin C. Camus; Stephen A. Raverty (Frontiers in Marine Science, 2021)

A Novel Orthoreovirus Isolated From Dead Stranded Harbor Seals From Puget Sound, Washington State, United States - Ole Nielsen; Thaís C. S. Rodrigues; Vsevolod L. Popov; Kuttichantran Subramaniam; Thomas B. Waltzek; Dyanna M. Lambourn; Stephen Raverty (Frontiers in Marine Science, 2021)
As part of an ongoing investigation of harbor seal ( Phoca vitulina ) mortalities within Puget Sound, Washington State, United States, between October 2007 and July 2008, 25 seal cases were submitted for histopathology and ancillary diagnostic testing, including additional attempted virus isolation. In vitro granular and refractile cytopathic effects (CPE) were consistently observed in Vero.DogSLAMtag cells inoculated with tissue homogenates from three seals. Transmission electron microscopy of infected Vero.DogSLAMtag cells revealed cytoplasmic clusters of icosahedral viral particles morphologically consistent with members of the family Reoviridae . The complete genome of a novel species within the genus Orthoreovirus , tentatively named phocid orthoreovirus 1 (PhRV1), was determined by next-generation sequencing and confirmed by rt-PCR in isolates from the three harbor seals. This is the first report of an orthoreovirus infection associated with dead stranded harbor seals. Aside from the CPE and ultrastructural findings, no consistent signalment, gross pathology, histopathology, or ancillary diagnostic findings were identified with PhRV1 infection. Further research is needed to determine the prevalence, tissue tropism, transmission, pathogenicity, zoonotic potential, and host range of orthoreoviruses in pinnipeds. This study demonstrates the value of thorough necropsy investigations and a multidisciplinary team approach to advance our understanding of marine mammal health.

The Emergence of Mucormycosis in Free-Ranging Marine Mammals of the Pacific Northwest - Jessica L. Huggins; Michael M. Garner; Stephen A. Raverty; Dyanna M. Lambourn; Stephanie A. Norman; Linda D. Rhodes; Joseph K. Gaydos; Jennifer K. Olson; Martin Haulena; M. Bradley Hanson (Frontiers in Marine Science, 2020)

Reemergence of Guadalupe fur seals in the U.S. Pacific Northwest: The epidemiology of stranding events during 2005–2016 - Erin D'Agnese; Dyanna Lambourn; James Rice; Debbie Duffield; Jessica Huggins; Terry Spraker; Stephen Raverty; Tetiana Kuzmina; Michael E. Grigg; Kristin Wilkinson; Steven Jeffries; Woutrina Smith (Marine Mammal Science, 2020)
Guadalupe fur seals (GFS), Arctocephalus philippii townsendi , an U.S. Endangered Species Act threatened pinniped, have recently reappeared in their historic range along the western seaboard of the continental United States. Starting 2005 through 2016, 169 GFSs stranded in Washington and Oregon, involving two designated unusual mortality events. The circumstances surrounding GFS strandings, mortality, and their increased presence in Oregon and Washington were analyzed during this study. Detailed necropsies, histopathology ( n = 93), and epidemiological analysis found three main causes of death (COD): emaciation (44%), trauma (29%), and infectious disease (19%) and the factors associated with overall strandings and emaciation. Trauma included many cases found associated with fisheries interactions and clustered near the mouth of the Columbia River, where high levels of commercial fishing occur. The most common pathogens found associated with disease were Toxoplasma gondii , Sarcocystis neurona , and gastrointestinal helminths. Seasonality and upwelling were associated with higher stranding numbers regardless of COD. Seasonal migration into the region, coinciding with postweaning, suggests young GFSs are in search of prey and habitat resources. Reemergence of GFSs is likely due to conservation efforts, which have been critical for species recovery in the region. Continued monitoring is needed as this vulnerable species continues to rebound.

Causes of Mortality in a Harbor Seal (Phoca vitulina) Population at Equilibrium - Elizabeth A. Ashley; Jennifer K. Olson; Tessa E. Adler; Stephen Raverty; Eric M. Anderson; Steven Jeffries; Joseph K. Gaydos (Frontiers in Marine Science, 2020)

Ice entrapment mortality may slow expanding presence of Arctic killer whales - Cory J. D. Matthews; Stephen A. Raverty; Dawn P. Noren; Lucassie Arragutainaq; Steven H. Ferguson (Polar Biology, 2019)

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Spatial and temporal analysis of killer whale ( Orcinus orca ) strandings in the North Pacific Ocean and the benefits of a coordinated stranding response protocol - Michelle M. Barbieri; Stephen Raverty; M. Bradley Hanson; Stephanie Venn‐Watson; John K. B. Ford; Joseph K. Gaydos (Marine Mammal Science, 2013)
Killer whales ( Orcinus orca ) are widely distributed throughout the world's oceans, yet little has been documented about their stranding patterns. Knowledge of stranding patterns improves our ability to examine and sample carcasses and provides a foundation for understanding killer whale natural history, diet, reproduction, anthropogenic stressors, emerging diseases, and patterns of unusual mortality. We compiled published and unpublished killer whale stranding data to describe stranding patterns in the North Pacific Ocean. Between 1925 and 2011, 371 stranded killer whales were reported in Japan (20.4%), Russia (3.5%), Alaska (32.0%), British Columbia (27.4%), Washington (4.0%), Oregon (2.7%), California (5.1%), Mexico (3.8%), and Hawaii (0.8%). Strandings occurred at all times of year, but regionally specific seasonal differences were observed. Mortality and annual census data from Northern and Southern Resident populations were extrapolated to estimate that across the North Pacific, an average of 48 killer whales die annually. However, over the last two decades, an average of only 10 killer whale carcasses were recovered annually in this ocean, making each event a rare opportunity for study. Publication of a standardized killer whale necropsy protocol and dedicated funding facilitated the number of complete postmortem necropsies performed on stranded killer whales from 1.6% to 32.2% annually.